Hubungan Antara Asupan Zat Gizi Makro, Aktivitas Fisik Dan Tingkat Stres Dengan Status Gizi Pada Siswa/I Kelas X Sman 51 Jakarta - Andra Vidyarini; Zahra Meillany (HB PRESS, 2025)
Coronary heart disease, diabetes mellitus, hypertension, and reproductive issues are more common in adolescents with either an insufficient or an excessive nutritional status. The objective of this research is to find out what the relationship is between class X students' nutritional state, stress, and their consumption of macronutrients at SMAN 51 Jakarta. The participants in this cross-sectional study were 90 adolescents from SMAN 51 Jakarta. making use of the whole sampling procedure for sampling. Adolescents' nutritional status was evaluated using IMT/U. We measured macronutrient consumption using the 2x24-hour meal recall technique, and we measured physical activity and stress levels using a questionnaire. Protein, lipid, and carbohydrate consumption were significantly associated with nutritional status (p = 0.001), however neither physical activity nor stress levels were found to be correlated (p = 0.891 and p = 0.109, respectively). Finally, increased protein, lipid, and carbohydrate consumption is associated with an increased risk of abnormal nutritional status in adolescents.